Prognostic implications of quantified coronary atherosclerosis and myocardial perfusion in diabetes - Mäenpää, Matias; Jukema, Ruurt A.; van Diemen, Pepijn; Bär, Sarah; Raijmakers, Pieter G.; Sprengers, Ralf; Driessen, Roel S.; Bax, Jeroen J.; Knaapen, Paul; Knuuti, Juhani; Danad, Ibrahim; Saraste, Antti; et al. (BioMed Central, 2026)
Background
Coronary artery disease (CAD) is a major contributor to cardiovascular events in individuals with diabetes. Quantification of coronary atherosclerotic burden is now feasible from coronary computed tomography angiography (CTA) whereas positron emission tomography (PET) enables quantitative assessment of myocardial perfusion. We studied the prognostic implications of quantitatively measured coronary plaque burden and myocardial perfusion in diabetic vs. non-diabetic patients with suspected CAD.
Methods
In this observational cohort study, 1311 symptomatic patients with suspected CAD underwent coronary CTA and [15O]H2O PET perfusion imaging. Coronary plaque burden was quantified using artificial intelligence–based analysis and reported as percent atheroma volume (PAV). Myocardial perfusion was assessed as regional stress myocardial blood flow (sMBF), with abnormal perfusion defined as ≥ 2 adjacent segments with sMBF < 2.3 ml/g/min. The composite endpoint was all-cause death, myocardial infarction (MI), or unstable angina pectoris (UAP) over 7 years.
Results
Among the 1311 patients, 251 (19%) had diabetes and 134 (10%) experienced an adverse event during follow-up. The annual event rate was low (0.8% [95% CI 0.6–1.1%]) in non-diabetic patients with normal myocardial perfusion and increased significantly with the presence of either diabetes (2.3% [95% CI 1.4–3.8%]), abnormal perfusion (2.6% [95% CI 2.1–3.3%]), or both (3.2% [95% CI 2.1–4.8%]) (p < 0.001). Among patients with normal myocardial perfusion, those with diabetes had two-fold PAV as compared with non-diabetic individuals (median 8.2% vs. 4.1%, p < 0.001). In multivariable Cox regression models, both PAV (HR 1.03 [95% CI 1.01–1.05] per 1% increase, p < 0.001) and regional sMBF (HR 1.04 [95% CI 1.01–1.07] per 0.1 ml/g/min decrease, p = 0.016) were independent predictors of adverse outcome in non-diabetic patients. In diabetic patients, only PAV (HR 1.04 [95% CI 1.01–1.07], p = 0.014) was predictive, whereas sMBF was not.
Conclusions
Coronary atherosclerotic plaque burden appears as an important predictor of long-term cardiovascular outcomes both in diabetic and non-diabetic patients. In patients with diabetes, normal myocardial perfusion does not necessarily imply low event risk, partly attributable to higher coronary plaque burden. Quantitative imaging methods for detailed CAD phenotyping shed light on the complex relationship between diabetes and clinical outcomes.